The Relationship Between Rape Myths, Revictimization by Law Enforcement, and Well-Being for Victims of Sexual Assault - Maiorano, Nicole (Violence against women, 2023)
Relationships between rape myths, revictimization, and postassault well-being were examined in a sample of adult victims of sexual assault (n = 88). Correlation, multiple regression, and path analyses investigated whether conformity to stereotypes of “real rape” or “real victim” was associated with revictimization and well-being. A possible mediating effect of revictimization on the relationship between rape myth conformity and well-being was assessed. The relationship between specific revictimization behaviors and emotions was also analyzed. Questioning victims’ resistance to the assault was correlated with revictimization emotions. “Real victim” characteristics were associated with well-being, but no mediating effect of revictimization was observed.